2000
DOI: 10.1007/s007050050025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of piscine and amphibian iridoviruses

Abstract: A total of 30 iridoviruses collected from Australia, South-East Asia, North America, South America and Europe were characterised. With the exception of the South-East Asian iridoviruses all viruses were found to belong to the genus Ranavirus. All viruses, except those originating from South-East Asia, cross-reacted with antisera against epizootic haematopoietic necrosis virus (EHNV). Viruses or virus-infected cells were examined using electron microscopy, SDS PAGE, restriction endonuclease (RE) digestion, DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
266
1
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(285 citation statements)
references
References 38 publications
15
266
1
3
Order By: Relevance
“…At the same time, size differences between viral particles from gourami and swordtail fish were not significant, which might imply that gouramies and swordtails that cohabited the same farm were crossinfected. Hyatt et al (2000) suggested that differences in particle sizes reflect subdivision within Ranavirus and among iridoviruses. Particle mean v-v from systemic infections observed in our study ranged from 156 to 181 nm, covering nearly the entire range of particle sizes listed by Hyatt et al (2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, size differences between viral particles from gourami and swordtail fish were not significant, which might imply that gouramies and swordtails that cohabited the same farm were crossinfected. Hyatt et al (2000) suggested that differences in particle sizes reflect subdivision within Ranavirus and among iridoviruses. Particle mean v-v from systemic infections observed in our study ranged from 156 to 181 nm, covering nearly the entire range of particle sizes listed by Hyatt et al (2000).…”
Section: Discussionmentioning
confidence: 99%
“…Hyatt et al (2000) suggested that differences in particle sizes reflect subdivision within Ranavirus and among iridoviruses. Particle mean v-v from systemic infections observed in our study ranged from 156 to 181 nm, covering nearly the entire range of particle sizes listed by Hyatt et al (2000). The mean particle size of the iridoviruses from guppies (GV6) and doctor fish (DFV) imported from South East Asia studied in the USA were 162 and 163 nm, respectively (Hedrick & McDowell 1995.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ranaviruses (Iridoviridae) are becoming increasingly associated with diseases in wild and cultured fishes, frogs, salamanders, and reptiles (Cunningham et al, 1996;Zupanovic et al, 1998;Hyatt et al, 2000;Zhang et al, 2001;Chinchar, 2002;De Voe et al, 2004;Pearman et al, 2004;Greer et al, 2005). Frog virus 3 (FV3), the best-characterized member and type species of the Ranavirus genus, is a large (165-169 nm) double-stranded DNA icosahedral virus that was originally isolated from the North American leopard frog, Rana pipiens (Chinchar, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…We believe that this is not due to insufficient outgroup divergence but due to the limited nature (i.e., possible homology) of the information contained in the partial sequence of the MCP of the virus being analyzed. Historically, short sequences of the MCP have been used to both classify ranaviruses and reconstruct their phylogenetic affinities (e.g., Hyatt et al, 2000), likely because of early evidence that the MCP was a good target for examining the relationships between closely related iridoviruses (Tidona et al, 1998). However, as we have shown in this study, the use of only a section of the MCP gene sequence may be misleading, especially when examining closely related viral isolates.…”
mentioning
confidence: 99%